Entrustment in plastic surgery residents’ informed consent taking for elective surgical procedures: a modified Delphi study - Aslam, Ayesha; Hanif, Maidah; Fayyaz, Humaira (Journal of the Pakistan Medical Association, 2025)
Objectives: To identify the competencies regarding entrustable professional activities among postgraduate plastic surgery residents for informed consent taking before any elective surgical procedure and to choose the appropriate assessment strategies. Method: The Modified Delphi study was conducted from July 2022 to January 2023 after approval from the ethics review committee of the Islamic International Medical College, Islamabad, Pakistan, and comprised two iterative rounds using the expert consensus approach involving consultant plastic surgeons serving in public, private and military teaching hospitals in Pakistan and abroad. Following literature search, competencies related to informed consent before elective plastic surgery procedures were identified. A 5-point Likert scale was formulated and the document was distributed online. Items reaching consensus level were included in the final document. The competencies that failed to reach the consensus level or needed amendments were sent in the second round along with additional questions regarding assessment strategies and supervision level. Data was analysed using SPSS 21. Results: Of the 51 plastic surgery consultants, 30(58.8%) responded in the first round. Out of 58 competencies initially identified, 49(84.5%) reached consensus level. No new entrustable professional activities or competencies were identified. Of the 9 competencies in the second round, consensus was achieved on 6(67.7%), with the response rate being 70%. The final set comprised 55 competencies under 8 entrustable professional activities. Conclusion: The entrustable professional activities identified provide a comprehensive competence-based assessment framework for taking informed consent in plastic surgery practice. Key Words: Plastic surgery residency, Entrustable professional activities, EPAs, Informed consent taking.